Menjamin Pinjaman dengan Cara Islami: Mengenal Konsep Gadai dalam Syariat Islam - Rahman, Fatmawati A; Nurjanna (PT Maju Malaqbi Makkarana, 2024)
Sharia pawn or rahn is a form of financing that allows individuals or companies to obtain short-term liquidity by pledging assets without permanently losing ownership. This study aims to gain a deeper understanding of the implementation of sharia pawn in Indonesia, including its advantages and challenges. This study is a qualitative study using a comprehensive literature study research method, the author of the data obtained was obtained from libraries in the form of books, articles, journals and scientific works with related topics, and using Google Scholar, Publish or Perish to search for references. Sharia pawn (rahn) is a sharia-based financial instrument that allows individuals or companies to obtain short-term liquidity by pledging assets without permanently losing ownership. It avoids usury elements and is based on the principle of mutual benefit. Sharia pawn has bright prospects in Indonesia along with the increasing public awareness to carry out economic activities according to sharia principles. However, the challenge is education and socialization to the community about its mechanisms and benefits.